Towards the Development of a Biocatalytic Cascade for the Synthesis of Iminosugars - Kuska, Justyna (2021)
Long and inefficient synthetic routes for the preparation of iminosugars impede the commercialisation and development of iminosugar based therapeutics. The excellent selectivity of enzymes makes them adapted to perform highly efficient cascade reactions. This project aimed to simplify the iminosugar synthesis and develop a one-pot enzymatic biocascade, which recruits transaminase, alcohol oxidase/alcohol dehydrogenase and imine reductase starting from aldose. Specifically, this work focused on the biocatalytic oxidation and reduction steps, with the particular attention paid to the first one. Chapter 5 explored regioselective oxidation of amino alcohols mediated by resting cells of Gluconobacter oxydans DSM 2003, which required Cbz protection of amine functionality. The biocatalyst was very efficient by transforming protected amino alcohols in the preparative-scale reactions in nearly quantitative conversions, generating four intermediates suitable for the synthesis of iminosugars. However, the requirement for amine protection impacted the initial cascade design, which was modified by adding two chemical steps: protection and deprotection. Chapter 6 investigated biocatalytic imine reduction of five-membered polyhydroxylated imines, which were the oxidation products with G. oxydans. Five known imine reductases were tested on these polar imine substrates to no avail. Chemical reduction and Cbz deprotection involving catalytic hydrogenation with Pd/C led to the final iminosugar products. This process resulted in two optically pure iminosugar compounds and two diastereoisomeric mixtures. The racemic mixtures were attempted to be deracemised with engineered variants of monoamine oxidases from Aspergillus niger; however, either of the enzymes accepted these highly polar substrates. Chapter 7 combined the established biocatalytic and chemical steps in the chemo- enzymatic route, which led to the synthesis of three iminosugar products starting from 2-deoxy-D-ribose, D-arabinose and D-ribose. The biocatalytic steps recruited a commercially available transaminase ATA-256 and Gluconobacter oxydans DSM 2003, while chemical steps involved Cbz-protection and reduction with Pd/C. The 5 overall synthesis required fewer steps than the reported sequences used for the same or similar targets, which also utilised carbohydrate-based starting materials.